2023
DOI: 10.1039/d3cp03977c
|View full text |Cite
|
Sign up to set email alerts
|

Threshold photoelectron spectroscopy and dissociative photoionization of benzonitrile

Jerry Kamer,
Domenik Schleier,
Merel Donker
et al.

Abstract: The threshold photoionization and dissociative ionization of benzonitrile (C6H5CN) were studied using double imaging photoelectron photoion coincidence (i2PEPICO) spectroscopy at the Vacuum Ultraviolet (VUV) beamline of the Swiss Light Source...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…87 Additional pathways for direct formation of the benzonitrile cation via association reactions have been proposed. 90 A closer look at the masses measured by the Cassini spacecraft 27 reveal strong features around m/z 103, 129, and 155 which are attributed to molecular formulas similar as observed in the benzonitrile •+ and acetylene reaction. Moreover, singly bonded (linked) aromatic compounds (polyphenyls 91 of.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 84%
“…87 Additional pathways for direct formation of the benzonitrile cation via association reactions have been proposed. 90 A closer look at the masses measured by the Cassini spacecraft 27 reveal strong features around m/z 103, 129, and 155 which are attributed to molecular formulas similar as observed in the benzonitrile •+ and acetylene reaction. Moreover, singly bonded (linked) aromatic compounds (polyphenyls 91 of.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 84%
“…2a . Threshold photoionization and dissociation ionization of benzonitrile has been recently studied by Kamer et al 2023 58 and showed accurate dissociation barriers of the different fragmentation channels. Both ortho -benzyne˙ + and bicyclic meta -benzyne˙ + are identified as the fragments and are used here to perform controlled (mass-selected) reactions with acetylene molecules inside the 22-pole ion trap which was maintained at a temperature of around 150 K. No spectroscopic evidence of monocyclic meta -benzyne˙ + has been found and this structure is therefore not participating in the reaction with acetylene.…”
Section: Resultsmentioning
confidence: 99%
“…The studied system is astrochemically relevant as both neutral benzonitrile 4 and o -benzyne 64 have been detected in the cold molecular cloud TMC-1. Upon UV photo-ionization or cosmic ray ionization the major HCN/HNC loss channel of benzonitrile, which has appearance energies reported in a range between 13.1 eV (ionization energy to cationic ground state + rate-determining HCN-loss barrier) 58 and 13.38 eV, 65 is accessible and reactive species can be formed. The chemistry of neutral o -benzyne with the small hydrocarbon allyl radical has previously been studied using double imaging photoelectron photoion coincidence spectroscopy (i 2 PEPICO) and showed the formation of the bicyclic molecule indene.…”
Section: Astrophysical Implications and Conclusionmentioning
confidence: 99%
“…Apart from these primary fragmentation channels, the parent ion, after losing a H atom, i.e., the fragment ion C 10 H 6 CN + , can further undergo dissociation into two different pathways, which are written in blue font in Figure 9. Recently, Kamer et al 2023 reported on the fragmentation of cyanobenzene, highlighting the seven major dissociation channels and a few other channels of lower fractional abundances, which includes the H loss channel.…”
Section: Dissociation Of Cyanopahsmentioning
confidence: 99%